How Do Non-Native Listeners Perceive Quality of Transmitted Voice? - Blaskova, Lubica; Holub, Jan (Communications - Scientific letters of the University of Zilina, 2008)
This paper describes the test methodology and results of speech transmission quality testing in the environment of non-native listeners; it means the communication language differs from the mother tongue of the test subjects. The tests were carried out based on ITU-T P.800 on a database of English speech samples affected by various coding distortions and background noise conditions. The subjects were pre-tested on their English proficiency. The subjective test results confirm a systematic and repeatable shift in subjective quality assessment performed by non-native listeners.